“Living in the Neolithic” – Impressions from the Experimental Archaeology Days of the University of Hamburg in Albersdorf in Summer 2014 - Tosca Friedrich (EXARC, 2015)
During the summer of 2014 more than 30 students from the Archaeological Institute of the University of Hamburg and four children participated in the practical archaeology week at the Stone Age Village in the Stone Age Park in Albersdorf. In preparation for this week in 2014 – which was the 10th anniversary of this seminar - the students attended a seminar at the University of Hamburg held by the lecturers T. Friedrich and B. Meller.